A Study of gainful employment of learners receiving skills training in the informal sector using Machine Learning - Raizan, Syed Ahsan; Alam, Sayed Tanjim (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.